Strangulated Umbilical Hernia: A Case Report - Tito Ade Putra; I Gede Swedagatha (HM Publisher, 2022)
Background: The abdominal wall hernia repair was one of the most frequently performed operations by general surgeons worldwide. The second most common hernia operation is repairs of umbilical hernia. It is estimated that 5% of individuals will develop an abdominal wall hernia over their lifetime. This study aimed to present a case of strangulated umbilical hernia. Case presentation: 51 years old male patient presented with sharp, non-radiating pain in the left abdominal region, obstipation, and noted bulge at his umbilicus about one year ago that did not shrink when he was lying down two days ago, the diameter about 7 cm. A plain Abdominal X-ray showed partial small bowel obstruction. The patient was taken to the operation theatre for laparotomy resection and reanastomose ileum and repair hernia defect with mesh. Prior to surgery, the patient received antibiotic therapy with Cefazolin 2gr intravenous, and the nasogastric decompression tube (NGT) was installed. On exploration, it was found necrotic ileum along 15 cm and performed resection, followed by end-to-end anastomosis. After the surgical procedure, the patient's hemodynamics was stable. Conclusion: Overall mortality and prognosis of hernia are influenced by whether the surgery was emergent or elective. Mortality is increased to up to 3% with emergency surgery for strangulated bowel, notably when bowel resection is performed.